Financing trade asset procurement and disposal on joint equity basis for MMES: an analysis of some vital Shariah and operational aspects - Sadique, Muhammad Abdurrahman (Islami Bank Training and Research Academy, 2010)
Debt financing arrangements utilised in financing trade goods and produce ready for disposal, usually based on structures adapted from factoring mechanisms, involve shortcomings from a shariah as well as a commercial perspective. Financing MMEs that have stocks ready for disposal could be advantageously carried out on equity basis. Measures that result in altering the agreed profit sharing ratio merely in view of the financial interests of one party could affects the consistency of equity relationships. Recognising additional costs incurred during the equity relationship as infusion of additional capital could lead to anomalous outcomes. Treating such expenses as debts incurred by the venture for which the partners are jointly liable could be more preferable from a shariah perspective. In financing asset procurement for MMEs, debt instruments appear especially inadequate. Adopting the equity structure as a comprehensive scheme embracing all stages from procurement of assets until their disposal, could help rectify some shortcomings inherent to debt financing arrangements.